2007
DOI: 10.1111/j.1365-2184.2008.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical results of autologous infusion of mobilized adult bone marrow derived CD34+ cells in patients with chronic liver disease

Abstract: Evidence is growing in support of the role of stem cells as an attractive alternative in treatment of liver diseases. Recently, we have demonstrated the feasibility and safety of infusing CD34(+) adult stem cells; this was performed on five patients with chronic liver disease. Here, we present the results of long-term follow-up of these patients. Between 1 x 10(6) and 2 x 10(8) CD34(+) cells were isolated and injected into the portal vein or hepatic artery. The patients were monitored for side effects, toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 25 publications
4
76
0
4
Order By: Relevance
“…hematopoietic cells harvested from a peripheral vein, avoiding the need for invasive procedures. Furthermore, several routes of cell administration have been investigated, included peripheral veins, the hepatic artery, and the portal vein [45][46][47][48][49][50][51][52][53][54]. In a randomized control study, Spahr et al reported that there were no significant differences in treatment outcomes when using autologous BMNCs harvested after G-CSF infusion through the hepatic artery, although several other randomized studies have shown favorable results, suggesting the usefulness of these therapies [50].…”
Section: Autologous Bone Marrow Cell Injection Therapy and Related Trmentioning
confidence: 99%
“…hematopoietic cells harvested from a peripheral vein, avoiding the need for invasive procedures. Furthermore, several routes of cell administration have been investigated, included peripheral veins, the hepatic artery, and the portal vein [45][46][47][48][49][50][51][52][53][54]. In a randomized control study, Spahr et al reported that there were no significant differences in treatment outcomes when using autologous BMNCs harvested after G-CSF infusion through the hepatic artery, although several other randomized studies have shown favorable results, suggesting the usefulness of these therapies [50].…”
Section: Autologous Bone Marrow Cell Injection Therapy and Related Trmentioning
confidence: 99%
“…The transplantation of BM-HSCs at a dose range of between 1 × 10 6 to 2 × 10 8 cells in liver cirrhosis patients either through the portal vein, peripheral vein, or he- [52] study provides evidence that infusion of CD34+ HSCs is relatively safe without any complications or side effects in the long term. Despite the diverse range of BM-HSCs (1 × 10 6 to 2.3 × 10 8 cells) per infusion, almost all the clinical studies have shown that these stem cells have the ability to restore liver function.…”
Section: Bone Marrow-derived Hematopoietic Stem Cells (Bm-hscs) In Aumentioning
confidence: 97%
“…Twelve weeks after infusion, the serum bilirubin and CPS levels were significantly reduced and ascites improved in 7 out of 9 patients. In another clinical study, the feasibility and the efficacy of CD34+ HSC infusion in five chronic liver disease patients was assessed [52]. In this study, patients were injected with a single dose of HSCs ranging between 1 × 10 6 to 2 × 10 8 cells via either the portal vein or hepatic artery.…”
Section: Bone Marrow-derived Mesenchymal Stem Cells (Bm-mscs) In Automentioning
confidence: 99%
“…Treatment of other degenerative diseases with stem cell therapy is possibly only in the research area, but with a potential expand to clinical practice in the near future. For example, recent published data has used human CD34+ adult bone marrow stem cells for the treatment of chronic liver disease and has shown an impressive outcome [Gordon et al, 2006;Levicar et al, 2008]. Haematopoietic stem cells have also being used in many clinical (Phase I) trails in the treatment of ischaemic heart disease, diabetes and other neurodegenerative diseases with an impressive preliminary outcome [Balsam and Robbins, 2005;Dimarakis et al, 2005;Levicar et al, 2007].…”
Section: Stem Cells and Clinical Relevance To Therapymentioning
confidence: 99%